Synthesized and characterization of organobentonites for anionic dye removal: application to real textile effluent. Issue 23 (15th October 2019) - Ayari, F.; Khelifi, S.; Trabelsi-Ayadi, M.
ABSTRACT: Clays have been considered as potential alternative adsorbents due to their high adsorptive property, abundance and non-toxic compounds. Adsorption of cationic dyes by natural clays has been studied and appreciable results have been reported, but few researchers have been interested in anionic dyes. Anionic dyes are widely used by the textile industries, yet they are toxic, non-biodegradable and hardly adsorbable on natural clay; modified clay (e.g. organoclay) has emerged as an alternative adsorbent. In this study, organobentonites were prepared with hexadecyltrimethylammonium bromide at three cation exchange capacity levels and used as adsorbents for the removal of, reactive blue II – an anionic dye used in Tunisian textile industry to dye jeans. Obtained organobentonite-labelled H i -bent ( I  = 1, 2 and 3) was characterized by several techniques in order to study the effect of a surfactant on texture and structure of the initial clay. H3 -bent and purified bentonite (Na-bent) were then tested as adsorbents. The amount of dye removal by H3 -bent (98%) was found to be around five times higher than that of Na-bent (19%). Adsorption process was well described by Freundlich, Dubinin–Radushkevic and Elovich isotherms model. Kinetic data were fitted by both pseudo-second-order and pseudo-first-order models. The use of Na-bent, as adsorbent, for real textile effluent treatment was tested, and significant results related to two other clay minerals were obtained. GRAPHICAL ABSTRACT: